Combined Systemic Intake of K-ATP Opener (Nicorandil) and Mesenchymal Stem Cells Preconditioned With Nicorandil Alleviates Pancreatic Insufficiency in a Model of Bilateral Renal Ischemia/Reperfusion Injury - ShamsEldeen, Asmaa Mohammed; El-Aal, Sarah A. Abd; Aboulhoda, Basma Emad; AbdAllah, Hend; Gamal, Sara Mahmoud; Hassan, Fatma E.; Mehesen, Marwa Nagi; Rashed, Laila Ahmed; Mostafa, Abeer; Sadek, Nermeen Bakr (Frontiers in Physiology, 2022)
We used nicorandil, a K-ATP channel opener, to study the role of these channels in the amelioration of renal ischemia/ reperfusion (I/R)-induced pancreatic injury, and the possible involvement of PI3K/Akt/mTOR signaling pathway. Forty-two male Wistar rats were included in this study, six were sacrificed for extraction of bone marrow mesenchymal stem cells (BM-MSCs) and conducting the in-vitro work, the others were included in vivo study and equally divided into 6 groups. Group 1 (sham control), but groups 2 to 6 were subjected to bilateral renal I/R: Group 2 (I/R); Group 3 (I/R-NC), treated with nicorandil; Group 4 (I/R-MSCs), treated with BM-MSCs; Group 5 (I/R-MSCC), treated with nicorandil-preconditioned BM-MSCs; Group 6 (I/R-NC-MSCC), treated with both systemic nicorandil & preconditioned BM-MSCC. Renal injury and subsequent pancreatic damage were detected in the I/R group by a significant increase in serum urea, creatinine, fasting glucose, and pancreatic enzymes. The pancreatic tissues showed a reduction in cellularity and a significant decrease in the expression of the cell survival pathway, PI3K/Akt/mTOR, in the I/R group compared to the control. Preconditioning MSCs with nicorandil significantly enhanced the proliferation assay and decreased their apoptotic markers. Indeed, combined systemic nicorandil and nicorandil- preconditioning maintained survival of MSC in the pancreatic tissue and amelioration of apoptotic markers and pancreatic TNF-α production. Histologically, all treated groups revealed better pancreatic architecture, and increased area % of anti-insulin antibody and CD31, which were all best observed in the NC-MSCC group. Thus, using K-ATP channel opener was efficient to enhance PI3K/Akt/mTOR expression levels (in vivo and in vitro).